Analisis Perspektif Hukum Ekonomi Syariah Terhadap Praktik Pengalihan Uang Kembalian Menjadi Barang - Sulthonuddin, Bung Hijaj; Yani, Neng Lilis (STAI Al Musaddadiyah Garut, 2025)
In buying and selling transactions, change plays an important role. However, in this modern era, coins are increasingly difficult to find, so many traders, including Toko Nuri in Cisurupan District, Garut Regency, replace change with candy. . Formulation of the problem: what is the transaction mechanism for transferring change for payments at Toko Nuri, what is the sharia economic law analysis regarding the form of transferring change for transactions at Toko Nuri. This research aims to understand the mechanism for transferring change and analyze sharia economic laws related to this practice. The method used is field research with a qualitative approach. The research results show that the transaction mechanism at Toko Nuri includes selecting goods, calculating, paying and transferring change. The practice of converting change into goods triggers mixed opinions from consumers; some feel uncomfortable and prefer change in cash, while others don't mind. From the perspective of sharia economic law, this practice can cause problems if it is not approved by consumers, considering the importance of consent and fairness in transactions. Keywords: Sharia Economic Law; transfer of change; other goods